Did Marx Fetishize Labor?. Issue 2 (2nd April 2016) - Düzenli, Faruk Eray
Abstract : Labor is often construed as the universal ontological ground of social life, the differentia specifica of human beings in most, but not all, Marxian accounts. But such a rendition fetishizes labor: a quality that arises as an effect of a network of relations (self-realizing productive activity, or the creator of all that exists) is conceived as the inherent, natural, and essential characteristic of an element of this network (labor). Despite occasional "slips, " Marx carefully avoids this fetishistic inversion: consequently, neither the creator of use-values nor the producer of values should be read as labor's innate or essential attribute. Rather, labor acquires these characteristics within Marx's discourse, rendering class relations visible.